THE EFFECT OF GOOD CORPORATE GOVERNANCE AND DIVIDEND POLICY ON STOCK PRICES (Study on IPO Issuers in 2021-2023) - Saputra, Mochammad Giffari; Matoati, Rindang (REVENUE: Jurnal Manajemen Bisnis Islam, 2025)
This study observed the phenomenon of underpricing in the average IPO stock prices during the period 2021–2023 up to 24 months after the IPO. Stock prices are influenced by internal company factors, the information of which can be obtained from annual reports. This study aimed to analyze the effect of good corporate governance, proxied by managerial ownership, board of directors, board of commissioners, and audit committee, as well as the effect of dividend policy, proxied by dividend payout ratio, on stock prices of IPO companies in 2021–2023. The research method used was multiple linear regression analysis using SPSS 27. The results showed that, partially, managerial ownership and board of directors had a significant effect on stock prices. Meanwhile, the board of commissioners, audit committee, and dividend payout ratio had no significant effect on stock prices. Simultaneously, managerial ownership, board of directors, board of commissioners, audit committee, and dividend payout ratio had a significant effect on stock prices.   Keywords: good corporate governance, dividend policy, stock price, IPO companies, Indonesia Stock Exchange.